Effect of polycarboxylic acid superplasticizer on sulphoaluminate cement based grouting material - Mingxuan ZHANG; Pengfei WANG; Tao YANG; Xiuru LIU; Changquan WU (Meitan kexue jishu)
With the increase of buried depth and mining strength, it is more and more difficult for ordinary Portland cement-based grouting reinforcement materials to meet the engineering requirements. Sulphoaluminate cement uses less energy than ordinary Portland cement, is more environmentally friendly, and is more in line with the concept of carbon peak/carbon neutral. However, its high price and fast setting limit its application in the field of grouting. Therefore, based on the reinforcement material of slag-desulfurization gypsum-sulfoaluminate cement terpolymer system, the macro and micro effects of different water-cement ratios and polycarboxylic acid water reducing agents on the material were studied, and the grouting performance was improved and optimized, and the optimized grouting reinforcement effect was verified through field engineering. The results show that: ① The mechanical strength of the material increases with the decrease of the water-cement ratio, and the maximum compressive strength at 28 d is 56.56 MPa; ② With the increase of polycarboxylic acid water reducer content, the setting time gradually extended, the fluidity gradually increased, and the compressive strength showed a trend of first increasing and then decreasing, with the maximum compressive strength of 75.09 MPa at 28 d; ③ According to the flower-time curve, the change of flowability with time can be divided into four stages: rapid stage (Ⅰ), slow stage, rapid stage (Ⅱ) and stable stage, and the best grouting period is in the slow stage; ④ The addition of polycarboxylic acid superplasticizer will delay the hydration process of cement, but at the same time will make the structure and morphology of the generated hydration products better; ⑤ Slag∶desulfurization gypsum∶thioaluminate cement optimal mix ratio (mass ratio) is 4∶1∶15, the addition of 0.3% water-reducing agent to improve the flow can meet the requirements of underground grouting, while having high strength, the best grouting period is the slow period (20−100 min) under the current ratio. ⑥ According to the screening ratio and method, guide the field grouting reinforcement project of the 4204 working surface of Hemay No.3 Mine, confirm that the process has a good grouting effect, can fully fill the cracks and effectively strengthen the surrounding rock, and the maximum deformation of the top and bottom plates and two sides is reduced from 432 mm and 324 mm before grouting to 233 mm and 153 mm after grouting. The deformation of surrounding rock is controlled effectively and has good economic benefits.